Intergenerational longitudinal associations between parental reading/musical traits, infants’ auditory processing, and later phonological awareness skills - Cantiani, Chiara; Dondena, Chiara; Molteni, Massimo; Riva, Valentina; Lorusso, Maria Luisa (Frontiers in Neuroscience, 2023)
The intergenerational transmission of language/reading skills has been demonstrated by evidence reporting that parental literacy abilities contribute to the prediction of their offspring's language and reading skills. According to the "Intergenerational Multiple Deficit Model", literacy abilities of both parents are viewed as indicators of offspring's liability for literacy difficulties, since parents provide offspring with genetic and environmental endowment. Recently, studies focusing on the heritability of musical traits reached similar conclusions. The "Musical Abilities, Pleiotropy, Language, and Environment (MAPLE)" framework proposed that language/reading and musical traits share a common genetic architecture, and such shared components have an influence on the heritable neural underpinnings of basic-level skills underlying musical and language traits.Here, we investigate the intergenerational transmission of parental musical and language-related (reading) abilities on their offspring's neural response to a basic auditory stimulation (neural intermediate phenotype) and later phonological awareness skills, including in this complex association pattern the mediating effect of home environment.One-hundred and seventy-six families were involved in this study. Through self-report questionnaires we assessed parental reading abilities and musicality, as well as home literacy and musical environment. Offspring were involved in a longitudinal study: auditory processing was measured at 6 months of age by means of a Rapid Auditory Processing electrophysiological paradigm, and phonological awareness was assessed behaviorally at 5 years of age.Results reveal significant correlations between parents' reading skills and musical traits. Intergenerational associations were investigated through mediation analyses using structural equation modeling. For reading traits, the results revealed that paternal reading was indirectly associated with children's phonological awareness skills via their electrophysiological MisMatch Response at 6 months, while maternal reading was directly associated with children's phonological awareness. For musical traits, we found again that paternal musicality, rather than maternal characteristics, was associated with children's phonological phenotypes: in this case, the association was mediated by musical environment.These results provide some insight about the intergenerational pathways linking parental reading and musical traits, neural underpinnings of infants' auditory processing and later phonological awareness skills. Besides shedding light on possible intergenerational transmission mechanisms, this study may open up new perspectives for early intervention based on environmental enrichment.